Methods and indicators of ensuring economic security of an industrial complex of the region - Samatov, T.I. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Ėkonomika, 2018)
The main components of economic security of an industrial complex of the region are defined. As factors of ensuring economic security are crossed with difficulty among themselves it’s reasonable to stop on allocation of three main types of economic security of an industrial complex of the region divided by types of means of production namely: production and trade, the equipment - technological and resource safety. Production and trade safety includes: production, transport and trade safety. The equipment - technological safety includes: innovative, technological and educational safety. Resource safety includes: raw materials, energy and financial and investment security. Methods and indicators of ensuring economic security of an industrial complex of the region which includes production and trade, technological and resource components are defined. The administrative sign defined depending on quality of strategically important administrative decisions made at the level of the management of the enterprise is accepted for calculation of an integrated indicator of economic security on the basis of which it is possible to modify and integrate indicators by all types of economic security